The Influence of Tax Compliance and Earnings Quality on Financial Performance (Evidence from Indonesia and Thailand) - Tarmidi, Deden; Murwaningsari, Etty; Umar, Haryono; Mayangsari, Sekar (International Journal of Emerging Trends in Social Sciences, 2020)
This study aims to analyse the effect of tax compliance and earnings quality on financial performance. Information on financial performance is needed by management for evaluating and determining targets, while external parties use it for various purposes. Several studies have found the effect of tax and earnings quality on corporate financial performance, with different results. Using 332 Indonesian and Thai manufacturing companies from 2014 to 2017 as a sample, this study did not find the effect of earnings quality on financial performance. In addition, a significant effect of tax compliance was found on financial performance. This result explains that tax has an important role in the sustainability business, therefore that management attention is needed in tax policy making so that it does not have a negative impact on the company. With the finding that tax compliance has a negative effect on financial performance, it is clear that there are still many taxpayers who have not utilized the taxation facilities from the government that should support the company’s financial performance.